The concept of competence and competence in education (Eurasian Research Bulletin, 2025)
The article discusses the scientific and theoretical foundations of the concepts of competence and competence in the process of literary education. The etymological, pedagogical and psychological analysis of the concepts of "competence" and "competence" in the system of literary education is highlighted.